Tax Analysis In The Distribution Of Inheritance: A Study Of Regulation And Implementation In Indonesia - Agung Satryo Wibowo; Rommy Hardyansah; Didit Darmawan; Risman; Ridwan Rahmawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Abstract This study analyzes the taxation arrangements in inheritance in Indonesia, particularly the tax obligations arising from the transfer of the testator's assets to the heirs. Inheritance involves movable and immovable assets that can become tax objects such as the Fees on Acquisition of Land and Building Rights (BPHTB) and Income Tax (PPh) on income from inherited assets. This research uses a normative legal approach to examine regulations such as Article 4 Paragraph (3) and Article 2 Paragraph (1) of the Income Tax Law, which regulate the imposition of taxes on undivided inheritance. The results show that strategies such as document consolidation, utilization of tax technology, and transparent reporting can improve heirs' compliance with tax obligations. In addition, the disclosure of financial information through the Common Reporting Standard (CRS) and Automatic Exchange of Information (AEoI) emphasizes the importance of reporting inheritance in the Annual Tax Return (SPT). By understanding the basis of tax imposition, correct reporting, and repayment mechanism, heirs can manage inheritance wisely and reduce the risk of conflict and legal sanctions. Keywords: Heirs, Income tax, Inheritance, Inheritance regulation , Land and building tax Taxation, Tax reporting